On the optimal parameters of GMSSOR method for saddle point problems. (May 2016) - Bi, Yanhui; Zhang, Naimin; Zhou, Lijuan
Abstract: For solving saddle point problems, SOR-type methods are investigated by many researchers in the literature. In this short note, we study the GMSSOR method for solving saddle point problems and obtain the optimal parameters which minimize the spectral (or pseudo-spectral) radii of the iteration matrices.